Pengaruh Konsentrasi Bahan Penguat terhadap Karakteristik Komposit Bioplastik Pati Talas (Xanthosoma sagittifolium) dan Kitosan - Sipayung, Hamonangan; Hartiati, Amna; Gunam, I.B (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 1 (2022): Maret, 2022)
Taro starch is a carbohydrate contained in plants, especially chlorophyll plant s . Naturally, starch contains amylose and amy lo pectin. Amylose gives a hard nature and gives a dark blue color on the iodine test, while amylopectin causes a sticky nature and does not cause a reaction. Chitosan is a linear polysaccharide consisting of the monomers N-acetylglucosamine (GlcNAc) and D-glucosamine (GlcN). Chitosan has the general formula (C6H9NO3)n or is referred to as poly(ß(1,4)-2-amino-2-Deoxy-D-glucopyranose). This study aims to determine the effect of the concentration of polyvinyl alcohol and polycaprolactone on the characteristics of the taro starch and chitosan bioplastic composites which produce the best bioplastic composites. This study used a randomized block design (RAK) with 6 treatments consisting of 3 levels of polyvinyl alcohol concentration and 3 levels of polycaprolactone concentration of 0%, 5% and 10% with taro starch and chitosan as raw materials 60:40. Each treatment was grouped into 3 based on the time of the bioplastic manufacturing process, so there were 18 experimental units. The variables observed were tensile strength, elongation at break, elasticity (Young's modulus), WVTR, swelling and biodegradation. The data were analyzed by analysis of variance (ANOVA) and continued with the Honest Significant Difference test if there was a significant effect. The results showed that the concentration of reinforcing material had a very significant effect on the characteristics of tensile strength, elongation at break, elasticity (Young's modulus), WVTR, swelling and biodegradation of taro starch and chitosan bioplastic composites. The best characteristic of taro starch and chitosan bioplastic composites was the concentration treatment of 10% polyvinyl alcohol with the greatest tensile strength 13.85 MPa, elongation at break 8.46%, elasticity 2.83 MPa, swelling 66.81%, WVTR 1, 85 g/m2day and biodegradation time for 7 days. Keywords : bioplastic composites, concentration, taro-chitosan starch, polyvinyl alcohol and polycaprolactone